Designing problem-driven instruction with online social media - Seo, Kay Kyeong-Ju; Pellegrino, Debra A.; Engelhard, Chalee (Emerald Publishing Limited : Information Age Publishing, 2011)
Designing Problem-Driven Instruction with Online Social Media has the capacity to transform an educator's teaching style by presenting innovative ways to empower problem-based instruction with online social media. Knowing that not all instructors are comfortable in this area, this book provides clear, systematic design approaches for instructors who may be hesitant to explore unchartered waters and offers practical examples of how successful implementations can happen.Furthermore, it is a reference for instructors who need to solve issues that occur when developing a class utilizing problem-driven instruction with online social media. With the recent exponential growth of Twitter and Facebook, the potential for social media as an educational venue brings an urgent call for researchers to increase their concentration in this area to investigate further the educational possibilities of this format. These factors combined illustrate the mission of this book that is to enable instructors in the areas of instructional design, multimedia, information science, technology, and distance learning to have an evidence-based resource for this underexplored niche in instruction.